The Meaning of Profit from the Perspective of Rice Farmers in Desa Kabalo, Kecamatan Tojo Barat, Kabupaten Tojo Una-Una - Nur Afifa; Sugianto; Tenripada; Ernawaty Usman (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to explore the meaning of profit from the perspective of rice farmers in Kabalo Village, Kecamatan Tojo Barat, Kabupaten Tojo Una-Una, by considering economic, social, and spiritual aspects. Unlike previous studies that tend to define profit narrowly as financial or accounting outcomes, this research highlights the multidimensional interpretation of profit based on local wisdom. Using a qualitative descriptive design with a phenomenological approach, data were obtained through field observations, in-depth interviews with three landowning farmers, and documentation. The analysis followed phenomenological stages, namely reduction, imaginative variation, and meaning synthesis, complemented by triangulation and member checks to ensure data validity. The findings reveal that profit is understood in three main dimensions: as a reserve for basic needs, as future savings that ensure security, and as the fruit of patience in the farming process. This study contributes to behavioral accounting literature by demonstrating how rural communities integrate material and immaterial values in defining profit, while also offering insights into the role of local wisdom in shaping accounting concepts in the farming economy.